La idea de autonomía en biología - Etxeberria, Arantza; Moreno, Álvaro (Logos. Anales del Seminario de Metafísica, 2007)
The aim of this article is to examine how the notion of biological autonomy may be linked to other notions of autonomy usual in philosophical discussions. Starting in the 70s, the Chilean biologists Humberto Maturana and Francisco Varela developed a theory of life as autopoiesis which gives rise to a new conception of autonomy: biological autonomy. The development of this concept implies the recovery of the notion of the organism in a scientific context in which biology and philosophy of biology are focused on the study of the gene by Molecular Biology and evolution by natural selection, by the so called Modern Synthesis. Here we try to show some implications of the concept of life as autonomy for current biology and how this concept can be related to other more usual ones in philosophy.